Coatings containing Janus particles that can form various microstructures

By introducing Janus particles and adhesive matrix emulsion into the coating, a variety of microstructure coatings are formed, which solves the problem of insufficient mechanical properties and functional durability of existing coatings, and achieves high-performance, durability and environmentally friendly coatings.

CN116640488BActive Publication Date: 2025-03-18TSINGHUA UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310633721.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-03-18
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

The existing solvent-based self-layer coatings have limitations in the selection of polymer resins and solvent media. The coating film formed has a single structure and function, and the mechanical properties, wear resistance and durability of specific functions are not ideal, which limits its application in multiple fields.

Method used

A coating containing Janus particles and an adhesive matrix emulsion was developed. The surface of Janus particles has organic partitioning and inorganic partitioning. Combining preferred polymers and modified silica partitioning, a coating of various microstructures is formed by regulating the polymer content and the dispersion of Janus particles.

Benefits of technology

It realizes environmentally friendly high-performance coating, with excellent mechanical properties and functional durability, good component compatibility of each layer of the coating, strong interface bonding between each layer, and is not easy to separate, and is suitable for applications in multiple fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116640488B_ABST
    Figure CN116640488B_ABST
Patent Text Reader

Abstract

The present invention relates to a coating comprising Janus particles and capable of forming a variety of microstructures, a method for preparing the coating, a method for preparing a coating using the coating, and the formed coating. The coating of the present invention comprises (A) Janus particles, the surface of which has organic partitions and inorganic partitions; and (B) an adhesive matrix emulsion, which contains one or more polymers; wherein the ratio of the mass of the (A) Janus particles to the mass of the polymer in the (B) adhesive matrix emulsion is (0.1-2):1. The coating of the present invention is environmentally friendly, has little harm to human health, and has a simple preparation process, wide applicability, low cost, and high economic benefits. The coating obtained from the coating of the present invention has excellent mechanical properties and functional durability. In the case of stratification, the components of each layer of the coating have good compatibility, and the interface bonding between the layers is strong and is not easy to separate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of coatings, and in particular relates to a coating comprising Janus particles and capable of forming a variety of microstructures. Background Art

[0002] In the coating industry, since a single-layer coating cannot meet multiple functional requirements, a multi-layer coating of primer, intermediate coating and topcoat is usually performed, which not only makes the construction process cumbersome and increases the cost, but also has the problem of low adhesion between coating layers, thus affecting the quality of the composite coating. In the 1970s, Funke et al. proposed self-stratified coatings, which can spontaneously form a composite coating of a multi-coating system after one coating, which not only simplifies the construction process, saves construction time, and reduces production costs, but also improves the interlayer adhesion between the coating layers and improves the various properties of the coating. In view of the good performance of self-stratified coatings, they have been used as coatings with multiple functions such as wear resistance, corrosion resistance, self-lubrication, and self-cleaning.

[0003] Traditional solvent-based self-stratifying coatings are usually made by mixing two or more polymers with different surface energies with a dispersion medium, and the solvent can be an organic solvent or water. The mixed coating is applied to the substrate at one time. During the evaporation of the medium or the curing of the polymer, the various polymer components spontaneously separate and migrate due to differences in their own surface energy or solubility in the medium, forming a gradient coating with varying performance and functions.

[0004] At present, the self-stratified coatings that are widely studied are mainly based on mixed coatings composed of resins with low surface energy (such as fluorinated acrylic resins) and resins with strong adhesion (such as acrylic resins, epoxy resins, and polyurethanes, etc.). During the film-forming process, the resin with low surface energy spontaneously migrates to the upper surface of the coating, so that the coating has weather resistance, chemical stability, corrosion resistance, hydrophobicity, oleophobicity, and stain resistance, etc.; Resins with strong adhesion, such as epoxy resins and acrylic resins, are deposited at the bottom to enhance the adhesion between the coating and the substrate. For example, in non-patent literature 1, an organic solvent-based coating is prepared, and a fluorinated polymer is blended with an epoxy resin. The mixed solvent is composed of a fast-evaporating solvent tetrahydrofuran and a slow-evaporating solvent toluene or xylene or n-butanol. Through the self-stratification technology, a gradient fluorinated coating that can be formed by one-time coating is obtained. The self-stratified coating has both the excellent surface properties of the fluorinated polymer and the excellent adhesion of the epoxy resin. In addition, in non-patent document 2, considering the harm of volatile organic compounds (VOCs) emitted by organic solvents to the environment, water is selected as a solvent, and acrylate emulsion and fluorinated acrylate emulsion are compounded into fluorinated self-stratifying coatings. The coating film has both the excellent hydrophobicity of pure fluorinated acrylate coatings and the excellent adhesion of pure acrylate emulsions. In addition, in non-patent document 3, fluorinated emulsions are blended with water-based epoxy resins to prepare water-based self-stratifying coatings. The blending system produces self-stratification, the bottom layer component is mainly epoxy resin, and the surface of the coating film is enriched with fluorinated resin to form a self-stratifying coating with a bottom surface.

[0005] Prior art literature:

[0006] Non-patent literature 1: Shi Yana, Zheng Zhaohui, Pan Yi, et al. Preparation and properties of environmentally friendly fluorinated epoxy self-stratifying coating with self-stratification effect [J]. Polymer Materials Science and Engineering, 2020, 36(3): 126-132;

[0007] Non-patent literature 2: Leng Changsong, Deng Jinni, Yin Lu, et al. Preparation and properties of fluorinated acrylate low surface energy coatings curable at high temperature based on self-stratification effect [J]. Polymer Materials Science and Engineering, 2015, 31(11): 151-155;

[0008] Non-patent literature 3: Qin Zonggen, Tu Weiping, Xia Zhengbin, et al. Study on the blending of epoxy emulsion and fluorine-containing emulsion [J]. Modern Chemical Industry, 2004, 24(5): 34-37. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] Existing solvent-based self-stratifying coatings have great limitations in the selection of polymer resins and solvent media, and the self-stratifying coating film structure and function formed are single, and the mechanical properties, wear resistance and durability of specific functions are not ideal, which limits the application of self-stratifying coatings in many fields (such as transportation vehicles and architectural decoration).

[0011] Specifically, 1) Traditional self-stratifying coatings need to follow the following principles when selecting polymer resins and solvents: (a) The two or more polymer components that make up the coating are thermodynamically incompatible, or have significant differences in surface energy, to ensure that during the solvent volatilization and polymer curing process, the component with low surface energy gradually migrates to the outer surface in contact with the air, and the component with high surface energy gradually migrates to the inner surface in contact with the substrate; (b) Organic solvent-based coatings need to use a specific mixed solvent as the medium, one of the solvents in the mixed solvent can dissolve two polymer resins at the same time, and the other solvent can only dissolve one of the polymer components, and self-stratification can only occur when the co-solvent evaporates first. In addition, the large amount of organic solvent volatilized during the molding process of organic solvent-based coatings has caused extremely serious harm to the environment.

[0012] 2) The coating structure formed by the existing self-stratified coating is mainly a double-layer structure in which a resin with low surface energy (such as fluorine-containing acrylate polymer) is located in the upper layer and a resin with high surface energy (such as acrylic polymer or epoxy resin) is located in the lower layer. The structural form is fixed and single, so its functionality is also relatively monotonous. In addition, the coating mainly provides mechanical properties (strength, hardness and wear resistance) with the help of high surface energy polymer resins, such as epoxy resins, and increases adhesion to the substrate, but the strength of polymer resins such as epoxy resins is not high and the wear resistance is poor. In addition, the functionality of the coating surface, such as hydrophobicity, is mainly provided by synthetic fluorine-containing acrylic polymers, but when the fluorine content in the polymer is high, the stability of the emulsion is poor. Therefore, the hydrophobicity of the synthetic fluorine-containing resin is not ideal. Therefore, the mechanical properties and functionality of the self-stratified coating materials prepared by the prior art are extremely limited.

[0013] Therefore, there is still a need for an environmentally friendly, durable coating having excellent mechanical properties and functions, and in particular, a self-stratifying coating having the characteristic that each layer is not easily separated in addition to the above.

[0014] Solutions for solving problems

[0015] In view of the problems existing in the prior art, the inventors have conducted in-depth research and developed a coating comprising Janus particles and an adhesive matrix emulsion.

[0016] Specifically, the present invention solves the problem of the present invention through the following solutions.

[0017] [1] A coating comprising

[0018] (A) Janus particles having organic and inorganic partitions on their surfaces; and

[0019] (B) an adhesive base emulsion comprising one or more polymers;

[0020] The ratio of the mass of the (A) Janus particles to the mass of the polymer in the (B) adhesive matrix emulsion is (0.1-2):1.

[0021] [2] The coating according to [1], wherein the organic partition on the surface of the (A) Janus particles is a polymer partition, and the inorganic partition is a silicon oxide partition, preferably a modified silicon oxide partition;

[0022] Preferably, the (A) Janus particles are in the shape of a snowman, wherein the mass ratio of the organic partition to the inorganic partition is 1:(0.5-4).

[0023] [3] A coating according to [1] or [2], wherein the content of the one or more polymers in the (B) adhesive matrix emulsion is 0.1 to 50% by mass, preferably 0.1 to 10% by mass or 30 to 50% by mass; preferably, the organic partition on the surface of the Janus particles contains the same polymer as the polymer in the (B) adhesive matrix emulsion.

[0024] [4] The coating according to any one of [1] to [3], wherein the polymer is selected from (meth)acrylate polymers, vinyl acetate polymers, polyurethanes, epoxy polymers, and styrene copolymers, and is preferably a (meth)acrylate polymer, the (meth)acrylate polymer comprising a structural unit derived from a (meth)acrylate monomer, and the (meth)acrylate monomer is preferably one or more selected from alkyl (meth)acrylates and epoxy-containing (meth)acrylates, more preferably one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and glycidyl (meth)acrylate, and even more preferably methyl (meth)acrylate and butyl (meth)acrylate;

[0025] Preferably, the styrene-based copolymer is selected from copolymers of styrene and butadiene.

[0026] [5] The coating according to [4], wherein the (meth)acrylate polymer further comprises a structural unit derived from an olefin monomer, wherein the olefin monomer is one or more selected from styrene, ethylene, propylene and any halogenated derivatives thereof; preferably, in the (meth)acrylate polymer, the structural unit derived from the (meth)acrylate monomer accounts for 50 mol% or more of the total structural units.

[0027] [6] The coating according to [1] or [2], wherein the modified silica partition is a hydrophobically modified silica partition, preferably a silica partition modified with a fluorine-containing silane coupling agent.

[0028] [7] The method for preparing a coating according to any one of [1] to [6], comprising the following steps:

[0029] Dispersing the (A) Janus particles in ethanol to obtain a Janus particle dispersion; and

[0030] The Janus particle dispersion is mixed with the (B) adhesive base latex.

[0031] [8] The method according to [7], wherein the content of the Janus particles in the Janus particle dispersion is 5 to 40% by mass.

[0032] [9] A method for preparing a coating, comprising the following steps:

[0033] applying the coating material described in any one of [1] to [6] on a surface of a substrate; and

[0034] The coating is allowed to cure.

[0035]

[10] A coating obtained by curing the coating material described in any one of [1] to [6], or a coating obtained by the preparation method described in [8].

[0036] Effects of the Invention

[0037] The coating of the present invention is environmentally friendly, has little harm to human health, has a simple preparation process, wide applicability, low cost, and high economic benefit. In addition, a coating with diversified structures and functions can be obtained through simple control means.

[0038] The coating obtained from the coating of the present invention can form a variety of microstructures, has excellent mechanical properties and functional durability, and in the case of stratification, the components of each layer of the coating have good compatibility, the interface bonding effect between the layers is strong, and it is not easy to separate.

[0039] The coating of the present invention can be widely used in multiple fields such as topcoat for vehicles such as automobiles, ships, and airplanes, architectural decorative coatings, and coatings for optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 (a) and (b) are respectively a low-magnification SEM image and a high-magnification SEM image of the upper surface of the coating 1 obtained in Example 1;

[0041] Figure 2 is a SEM image of the cross section of coating 1 obtained in Example 1;

[0042] Figure 3 (a) and (b) are low-magnification SEM images and high-magnification SEM images of coating 2 obtained in Example 2;

[0043] Figure 4 is a SEM image of the upper surface of coating 3 obtained in Example 3;

[0044] Figure 5 is a SEM image of the cross section of coating 3 obtained in Example 3;

[0045] Figure 6 (a) to (c) are photos of water contact angle test results of coating 1 of Example 1, coating 2 of Example 2, and coating 3 of Example, respectively;

[0046] Figure 7 (a) and (b) are respectively the SEM photo of coating 3 of Example 3 after the test and the photo of the water contact angle result in the durability test;

[0047] Figure 8 The present invention is a schematic diagram of a method for preparing a self-stratifying coating and obtaining a coating in one embodiment of the present invention. DETAILED DESCRIPTION

[0048] <Terms and Definitions>

[0049] In the present specification, the term "(meth)acrylate polymer" includes a homopolymer of a (meth)acrylate monomer and a copolymer of a (meth)acrylate monomer and other monomers.

[0050] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0051] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0052] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0053] In this specification, the use of "optionally" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0054] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0055] In this specification, the references to "preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0056] <Paint>

[0057] An object of the present invention is to provide a coating comprising

[0058] (A) Janus particles having organic and inorganic partitions on their surfaces; and

[0059] (B) an adhesive base emulsion comprising one or more polymers;

[0060] The ratio of the mass of the (A) Janus particles to the mass of the polymer in the (B) adhesive matrix emulsion is (0.1-2):1.

[0061] The components and content of the self-stratifying coating of the present invention are described in detail below.

[0062] (A) Janus particles

[0063] In the coating of the present invention, component (A) is Janus particles. Janus materials are particles having two different chemical components on the surface and being strictly partitioned.

[0064] In one embodiment, the organic partition on the surface of the (A) Janus particle is a polymer partition. The polymer partition of the Janus particle can select a specific polymer according to the actual application scenario, such as an acrylate soft polymer with film-forming properties, a copolymer of acrylate and methacrylate that improves the weather resistance of the material, etc.

[0065] In a specific embodiment, the polymer is selected from (meth)acrylate polymers, vinyl acetate polymers, polyurethanes, epoxy polymers, copolymers of (meth)acrylate and styrene (e.g., derived from styrene-acrylic emulsions), and copolymers of styrene and butadiene (e.g., derived from styrene-butadiene emulsions).

[0066] Preferably, the polymer is a (meth)acrylate polymer, which contains structural units derived from (meth)acrylate monomers, and the (meth)acrylate monomers are preferably one or more selected from alkyl (meth)acrylates and epoxy-containing (meth)acrylates, more preferably one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and glycidyl (meth)acrylate, and even more preferably methyl (meth)acrylate and butyl (meth)acrylate.

[0067] In one embodiment, the (meth)acrylate polymer further comprises a structural unit derived from an olefin monomer, wherein the olefin monomer is one or more selected from styrene, ethylene, propylene and any halogenated derivatives thereof.

[0068] The (meth)acrylate monomers and olefin monomers listed above can be used alone or in combination of two or more. In the case of combining multiple monomers, the (meth)acrylate polymer can be a random copolymer, block copolymer or graft copolymer containing structural units derived from the corresponding monomers.

[0069] In one embodiment, in the (meth)acrylate polymer, the structural unit derived from the (meth)acrylate monomer accounts for 50 mol % or more of the total structural units.

[0070] In one embodiment, the inorganic partitions on the surface of the (A) Janus particles are silicon oxide partitions, preferably modified silicon oxide partitions.

[0071] The inorganic partition of Janus particles is silicon oxide, which can give the coating rigidity and wear resistance without complicated high-temperature curing processes. At the same time, the silanol group on one end of the silicon oxide provides the possibility of functional modification of Janus particles, such as grafting fluorinated silane coupling agents to make the coating hydrophobic or even super-hydrophobic, or grafting magnetic, light, temperature and other responsive polymers to make the coating intelligently responsive, which can greatly improve the functionality of the coating. The functionalized silicon oxide end has higher strength and stiffness than polymer resins, which can improve the durability of the coating function, thus achieving a high-performance coating with strong mechanical properties, diversified functions and durability.

[0072] In a preferred embodiment, the polymer partition on the surface of the Janus particle contains the same polymer as in the adhesive matrix emulsion, and the other side is hydrophobically modified silica, so that the Janus particle has good dispersibility in the coating, thereby facilitating self-stratification. In addition, since one side of the Janus particle is the same polymer as in the adhesive matrix emulsion, it has excellent compatibility with the adhesive matrix, and thus has good adhesion to the adhesive matrix, and the interfacial bonding strength between the Janus particle and the adhesive is high, which is beneficial to the mechanical properties and durability of the coating.

[0073] In one embodiment, the Janus particles are in the shape of a snowman, wherein the mass ratio of the organic partition to the inorganic partition is 1:(0.5-4).

[0074] In one embodiment, the overall size of the Janus particle is 50-100 nm. Here, "overall size" refers to the size of the longest diameter of the Janus particle.

[0075] In one embodiment, in the Janus particles, the mass ratio of the organic partition to the inorganic partition is 1:(0.5-4), preferably 1:(0.5-2).

[0076] In one embodiment, the modified silica is a hydrophobically modified silica, preferably a silica modified with a fluorine-containing silane coupling agent, thereby imparting hydrophobicity to the coating.

[0077] Examples of fluorine-containing silane coupling agents include, but are not limited to, trifluoropropane trimethoxysilane, trifluoropropane triethoxysilane, tridecafluorooctyl trimethoxysilane, tridecafluorooctyl carboxy triethoxysilane, 1H,1H,2H,2H-perfluoroheptadecantrimethyloxysilane, and the like.

[0078] Component (B) Adhesive Base Emulsion

[0079] The (B) adhesive base emulsion used in the present invention contains one or more polymers selected from the group consisting of one or more polymers described above for the polymer in the organic partition of the Janus particles.

[0080] Preferably, the one or more polymers contained in the (B) adhesive base emulsion are the same polymers as those in the organic partition of the Janus particles.

[0081] In one embodiment, the content of the one or more polymers in the (B) adhesive matrix emulsion is 0.1 to 50% by mass, preferably 0.1 to 10% by mass or 30 to 50% by mass.

[0082] In one embodiment, the content of the polymer in the adhesive base emulsion is 0.1 to 10% by mass or 30 to 50% by mass. By making the content of the polymer in the adhesive base emulsion within the above range, a self-stratifying coating can be obtained.

[0083] In one embodiment, the content of the one or more polymers in (B) the adhesive base emulsion is 0.1 to 5% by mass, preferably 0.5 to 3% by mass, and more preferably 0.8 to 2% by mass.

[0084] In this embodiment, after curing, the coating of the present invention forms a coating structure in which Janus particles aggregate to form a micro-nano-scale rough structure distributed in the upper layer.

[0085] In one embodiment, the content of the one or more polymers in (B) the adhesive base emulsion is 30 to 50% by mass, for example, 32 to 48% by mass, 35 to 45% by mass, or 38 to 42% by mass.

[0086] In this embodiment, the coating of the present invention forms a coating structure in which Janus particles are aggregated in the lower layer after curing.

[0087] After the coating of the present invention is cured, a structure in which Janus particles are aggregated in the upper or lower layer of the coating can be formed, or a non-stratified homogeneous coating structure can be formed. The inventors have found that the coating structure is related to the content of the one or more polymers in (B) the adhesive matrix emulsion, and it is speculated that it is related to the competition between the bonding film-forming time of the polymer in (B) the adhesive matrix emulsion and its diffusion time. Specifically, when the polymer concentration in the adhesive matrix emulsion is low, the solvent evaporation time is long, and the Janus particles can be fully diffused to the entire coating; when the polymer concentration in the adhesive matrix emulsion is high, the solvent evaporation causes the surface colloid to quickly bond and form a film, and the osmotic pressure gradient generated by the concentration change pushes the Janus particles to move downward, so they aggregate in the lower layer; when the polymer concentration in the adhesive matrix emulsion is extremely low, the polymer colloid cannot form a spatial barrier to the hydrophobic Janus particles, and the Janus particles are unstable and assembled into a nanoflower structure. This hydrophobic nanoflower structure migrates to the surface layer of the coating in contact with the air due to its low surface energy, and is therefore distributed in the upper layer of the coating after curing.

[0088] The adhesive matrix emulsion used in the present invention can be obtained commercially, for example, the brand of BASF Chemical Co., Ltd. is 7015 aqueous emulsion of acrylate and methacrylate copolymer, and 7026G, 7066, 7051X emulsion.

[0089] Other components

[0090] In one embodiment, the coating of the present invention further comprises ethanol, wherein the content of ethanol is preferably 1 to 80 wt%, more preferably 2 to 70 wt%, and further preferably 3 to 65 wt%.

[0091] Component content

[0092] In the present invention, the mass ratio of (A) Janus particles to (B) polymer in the adhesive matrix emulsion is (0.1-2): 1

[0093] In one embodiment, the ratio of the mass of the organic partition in (A) the Janus particle to the mass of the polymer in (B) the adhesive matrix emulsion is 1:(0.5-2).

[0094] In one embodiment, in the coating of the present invention, the mass content of (A) Janus particles is 1 to 50%.

[0095] In one embodiment, the solid content of the coating of the present invention is 0.5 to 30 wt %, preferably 1 to 30 wt %, and more preferably 1 to 25 wt %.

[0096] <Method for preparing coating>

[0097] Another object of the present invention is to provide a method for preparing the coating of the present invention, which comprises the following steps:

[0098] Dispersing the (A) Janus particles in ethanol to obtain a Janus particle dispersion; and

[0099] The Janus particle dispersion is mixed with the (B) adhesive base latex.

[0100] In one embodiment, the content of Janus particles in the Janus particle dispersion is 5-40% by mass. Ethanol is used as a solvent in the Janus particle dispersion. Hydrophobic Janus particles have good dispersibility in ethanol, and ethanol volatilization does not cause harm to organisms.

[0101] In one embodiment, the Janus particle dispersion can be mixed with the (B) adhesive matrix latex under mechanical stirring or ultrasonic conditions.

[0102] The Janus particles used in the present invention can be prepared by methods known in the art, for example, by the method described in patent document CN114989363A.

[0103] In one embodiment, the method for preparing the coating of the present invention further comprises the step of preparing Janus particles.

[0104] In a specific embodiment, polymer (preferably polymer in adhesive matrix emulsion) particles are used as seed balls, silicon oxide precursor is used as monomer, and polymer@SiO2 composite Janus particles are synthesized by a one-step method based on reaction-induced phase separation. The particle surface has two partitions of polymer and SiO2 at the same time, and the surface of one side of SiO2 contains silanol active reactive groups. Optionally, the surface of one side of SiO2 of the particle is further hydrophobically modified, for example, by using a fluorine-containing silane coupling agent to obtain amphiphilic Janus particles.

[0105] In a more specific embodiment, the steps of preparing the amphiphilic Janus particles include:

[0106] (1) adding an emulsion composition containing a silicon oxide precursor to a seed emulsion to obtain a mixed solution;

[0107] (2) subjecting the silicon oxide precursor in the mixed solution to polymerization and hydrolysis condensation reaction to obtain a composite Janus particle precursor;

[0108] (3) The composite Janus particles are dispersed in a solvent, and a silane coupling agent for hydrophobic modification is dissolved therein and reacted to hydrophobically modify silicon oxide in the composite Janus particles.

[0109] In the present invention, there is no particular restriction on the silicon oxide precursor. In some specific embodiments, the silicon oxide precursor is preferably a silane coupling agent containing a double bond. The specific examples of the silane coupling agent containing a double bond include, but are not limited to, 3-(methacryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(methacryloyloxy)propyltripropoxysilane, 3-(methacryloyloxy)propyltrichlorosilane, vinyltrimethoxysilane, vinyltri(2-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrichlorosilane, allyltrimethoxysilane, allyltriethoxysilane, allyltrichlorosilane, 3-butylenetrimethoxysilane, 3-butylenetriethoxysilane, 3-butylenetrichlorosilane, isobutyltrimethoxysilane, isobutyltriethoxysilane, isobutyltrichlorosilane. These double bond-containing silane coupling agents may be used alone or in combination of two or more.

[0110] In the present invention, the seed emulsion is an emulsion containing polymer particles (preferably the polymer in the adhesive base emulsion).

[0111] In one embodiment, the above (2) is performed under an inert gas atmosphere, more preferably at a temperature of 50-85° C. When the silicon oxide precursor is polymerized, polymerization-induced phase separation occurs, and the polymerized silicon oxide precursor undergoes hydrolysis and condensation to form composite Janus particles.

[0112] In one embodiment, the solvent in (3) above can be appropriately selected as needed, as long as it does not cause damage to the composite Janus particles. In some preferred embodiments, specific examples of the solvent include, but are not limited to, methanol, ethanol, isopropanol, benzene, toluene, xylene, pentane, hexane, octane, cyclohexane, tetrahydrofuran, dioxane, ether, anisole, diphenyl ether, n-hexane, N,N-dimethylformamide, 1,4-dimethyl sulfoxide, N-methylpyrrolidone, acetone, cyclohexanone, glycidyl acetate, chlorobenzene, dichlorobenzene, dichloromethane, chloroform, carbon tetrachloride, etc.

[0113] <Coating preparation method and coating>

[0114] An object of the present invention is to provide a method for preparing a coating, which comprises the following steps:

[0115] Applying the coating of the present invention on the surface of a substrate; and

[0116] The coating of the present invention is allowed to cure.

[0117] The present invention has no particular limitation on the coating method, and the coating can be performed by any suitable method known in the art, for example, by spray coating, roller coating, spin coating, etc.

[0118] In one embodiment, curing can be performed at room temperature (20-30°C) or under heating (at a temperature above 30°C).

[0119] The present invention has no particular limitation on the substrate, which may be the outer shell of vehicles such as cars, ships, and airplanes, as well as the wall of a building, the outer shell of an optoelectronic device, and the like.

[0120] The present invention also correspondingly relates to a coating obtained from the coating material of the present invention or from the coating preparation method of the present invention.

[0121] Example

[0122] The present invention is further described by enumerating specific implementation cases below. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content recorded in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the present invention equally.

[0123] The adhesive matrix emulsion used in the following examples is an aqueous emulsion of a copolymer of acrylate and methacrylate (glass transition temperature is 14.1° C.), purchased from BASF Chemical Co., Ltd., with the brand name 7015, solid content is 50wt%, pH is 7.0-9.0.

[0124] Example 1

[0125] 1) Preparation of hydrophobic Janus particles

[0126] a) 3-(methacryloyloxy)propyltrimethoxysilane (MPS, KH570 silane coupling agent) was used as a silicon oxide precursor. 3% by mass of sodium dodecyl sulfate (SDS) relative to the total amount of MPS was dissolved in deionized water, and after ultrasonic dispersion, 1% by mass of potassium persulfate (KPS) relative to the total amount of MPS was added, and then MPS was added, and ultrasonic treatment was performed in an ice water bath to obtain an MPS emulsion composition as a silicon oxide precursor, wherein the content of MPS in the emulsion composition was 20% by mass.

[0127] b) In adhesive matrix emulsion Deionized water was added to 7015 to obtain a seed emulsion in which the content of the copolymer as seed particles was 2% by mass.

[0128] c) under mechanical stirring at a speed of 300 r / min, the MPS emulsion composition obtained in a) is added dropwise to the seed emulsion obtained in b) in an amount such that the mass ratio of the acrylic copolymer particles to the MPS is 1 / 2 to obtain a mixed solution. Nitrogen is passed through the mixed solution for 30 minutes to remove oxygen in the system, the temperature is raised to 70° C., and the MPS is polymerized for 24 hours under mechanical stirring at a speed of 300 r / min to obtain an emulsion containing composite Janus particles; and the obtained composite Janus particles are then washed with deionized water;

[0129] d) The Janus particles obtained above are dispersed in ethanol, and a fluorinated silane coupling agent 1H,1H,2H,2H-perfluoroheptadecantrimethyloxysilane is added, the mass ratio of the Janus particles to the fluorinated silane coupling agent is 1:1, the resulting mixture is magnetically stirred at 40° C., the Janus particles are fluorinated, the obtained particles are centrifuged and washed with ethanol to remove unreacted fluorosilane coupling agent, and hydrophobic Janus particles (M-JPs) modified with fluorosilane coupling agent are obtained.

[0130] e) The obtained hydrophobic Janus particles (M-JPs) were redispersed in ethanol to prepare a M-JPs dispersion with a mass fraction of 15 wt.%.

[0131] 2) In adhesive matrix emulsion Deionized water was added to 7015 to prepare a base adhesive emulsion with a polymer mass fraction of 1 wt%;

[0132] 3) The M-JPs dispersion obtained in 1) is mixed with the base adhesive emulsion in 2) so that the mass of the hydrophobic Janus particles and the polymer particles in the base adhesive emulsion remain the same, and the coating 1 is obtained after ultrasonic dispersion.

[0133] Example 2

[0134] Coating 2 was prepared in the same manner as in Example 1, except that in step 2), the base adhesive emulsion was formulated to have a polymer mass fraction of 20 wt%.

[0135] Example 3

[0136] The self-stratifying coating 3 was prepared in the same manner as in Example 1, except that in step 2), the base adhesive emulsion was formulated to have a polymer mass fraction of 40 wt%.

[0137] <Evaluation>

[0138] Surface and cross-sectional morphology

[0139] 300 μL of coating 1, coating 2 and coating 3 were respectively applied on a glass substrate and dried naturally at room temperature to obtain coating 1, coating 2 and coating C after the polymer was cured.

[0140] The SEM images of the upper surfaces of coatings 1, 2, and 3, and the SEM image of the cross section of coating 1 were obtained as follows: Figures 1 to 5 shown.

[0141] Scanning electron microscope (SEM) model: JSM-7900F, JEOL;

[0142] Test conditions: 5kV;

[0143] Sample preparation method: For cross-section photographs, the samples were broken directly at room temperature.

[0144] Depend on Figure 1 As can be seen from (a) and (b), in coating 1, Janus particles tend to assemble into clusters. During the curing process of solvent evaporation, Janus particle clusters aggregate in the system to form micro-nanoscale rough structures distributed in the upper layer of the coating.

[0145] Depend on Figure 2 It can be seen that the upper layer of coating 1 is a rough layer formed by Janus particle clusters, while the lower layer of coating 1 has a lower content of Janus particles and a higher content of adhesive matrix, forming a polymer layer filled with Janus particles. The elastic modulus of this layer measured by nanoindentation is 1.3 GPa, and the nanoindentation surface hardness measured by nanoindentation is 10 MPa.

[0146] Depend on Figure 3It can be seen that coating 2 is not stratified, and the Janus particles do not form clusters, but are evenly dispersed on the coating surface and throughout the coating, and there is almost no micron-scale rough structure on the coating surface.

[0147] Depend on Figure 4 and 5 It can be seen that coating 3 forms an obvious self-stratified structure, with the upper layer being a smooth film formed by the adhesive emulsion and the lower layer being an aggregated layer of Janus particles. The upper layer of this layered structure gives the coating appearance characteristics, such as gloss, smoothness, coloring, and weather resistance, while the lower layer of aggregated hydrophobic Janus particles has good adhesion to the substrate and has an anti-corrosion function, achieving structural-functional integration.

[0148] Hydrophobicity

[0149] The test was performed using an OCA20 contact angle meter (Dataphysics Instruments GmbH, Germany) at 23°C using the drop method. 3 μL of deionized water was dropped on the sample surface, and the contact angle was measured after the drop was stable.

[0150] The contact angle test results of coating 1, coating 2 and coating 3 are shown as follows: Figure 6 As shown in (a) to (c).

[0151] Depend on Figure 6 It can be seen that the low surface energy Janus particles, combined with the micro-nanoscale rough structure, make the surface of coating 1 super hydrophobic, and the water contact angle reaches 153°; for coating 2, the evenly distributed low surface energy Janus particles make coating 2 hydrophobic, and the water contact angle of the coating surface is 110°; the water contact angle of the surface of coating 3 is similar to that of the adhesive itself, which is 88°, and has a certain degree of hydrophobicity.

[0152] Durability

[0153] The coating 2 and coating 3 were rubbed for 300 cycles using 1000-grit sandpaper and a 200-g weight. The surface SEM image of the rubbed coating 3 was obtained according to the above method, and the water contact angle was tested. The results were as follows: Figure 7 As shown in (a) and (b).

[0154] Coating 3 still exhibits superhydrophobicity after 300 friction cycles, with a water contact angle of 152° and a rolling angle of 5.5°.

[0155] Coating 2 still has significant hydrophobicity after 300 cycles of friction, with a water contact angle of 152°

[0156] Industrial Applicability

[0157] The self-stratifying coating of the present invention can be widely used in multiple fields such as topcoats for vehicles such as automobiles, ships, and airplanes, as well as architectural decorative coatings, optoelectronic device coatings, and the like.

Claims

1. A self-stratifying coating, characterized in that: Include (A) Janus particles with organic and inorganic partitions on their surface; and (B) an adhesive base emulsion comprising one or more polymers; Wherein, the mass ratio of the (A) Janus particles to the mass ratio of the (B) polymer in the adhesive matrix emulsion is (0.1-2):1; The content of the one or more polymers in the (B) adhesive matrix emulsion is 0.1-5% by mass or 30-50% by mass; The organic partitions on the surface of the (A) Janus particles contain the same polymer as the polymer in the (B) adhesive matrix emulsion; The polymer is selected from (meth)acrylate polymers, vinyl acetate polymers, polyurethane, and epoxy polymers; The (meth)acrylate polymer comprises a structural unit derived from a (meth)acrylate monomer, wherein the (meth)acrylate monomer is one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, n-hexyl (meth)acrylate, cyclohexyl (meth)acrylate, and glycidyl (meth)acrylate.

2. The self-stratifying coating according to claim 1, characterized in that The organic partition on the surface of the (A) Janus particle is a polymer partition, and the inorganic partition is a silicon oxide partition.

3. The self-stratifying coating according to claim 2, characterized in that The (A) Janus particles are snowman-shaped, wherein the mass ratio of the organic partition to the inorganic partition is 1:(0.5-4).

4. The self-stratifying coating according to claim 2, characterized in that The inorganic partition is a modified silicon oxide partition.

5. The self-stratifying coating according to claim 1, characterized in that The (meth)acrylate monomers are one or two selected from methyl (meth)acrylate and butyl (meth)acrylate.

6. The self-stratifying coating according to claim 1, characterized in that The (meth)acrylate polymer further comprises a structural unit derived from an olefin monomer, wherein the olefin monomer is one or more selected from styrene, ethylene, propylene and any halogenated derivatives thereof.

7. The self-stratifying coating according to claim 6, characterized in that In the (meth)acrylate polymer, the structural unit derived from the (meth)acrylate monomer accounts for 50 mol % or more of the total structural units.

8. The self-stratifying coating according to claim 4, characterized in that The modified silicon oxide partition is a hydrophobically modified silicon oxide partition.

9. The self-stratifying coating according to claim 8, characterized in that The modified silicon oxide partition is a silicon oxide partition modified by a fluorine-containing silane coupling agent.

10. The method for preparing a self-stratifying coating according to any one of claims 1 to 9, characterized in that: The following steps are involved: Dispersing the (A) Janus particles in ethanol to obtain a Janus particle dispersion; and The Janus particle dispersion is mixed with the (B) adhesive base latex.

11. The preparation method according to claim 10, characterized in that: The content of Janus particles in the Janus particle dispersion is 5 to 40% by mass.

12. A method for preparing a coating, characterized in that: The following steps are involved: Applying the self-stratifying coating according to any one of claims 1 to 9 on the surface of a substrate; and The self-stratifying coating is cured.

13. A coating obtained by curing the self-stratifying coating according to any one of claims 1 to 9, or a coating obtained by the preparation method according to claim 12.

Citation Information

Patent Citations

  • Composite Janus particle and manufacturing method thereof

    CN114989363A

  • Composite Janus particle, method for producing same, coating layer, and laminate

    CN115322509A

  • Water-based acrylic coating added with Janus silicon dioxide nanosheets and preparation method of water-based acrylic coating

    CN115678365A